Organelle biogenesis and intracellular lipid transport in eukaryotes. - Voelker, D R (1991)
The inter- and intramembrane transport of phospholipids, sphingolipids, and sterols involves the most fundamental processes of membrane biogenesis. Identification of the mechanisms involved in these lipid transport reactions has lagged significantly behind that for intermembrane protein traffic until recently. Application of methods that include fluorescently labeled and spin-labeled lipid analogs, new cellular fractionation techniques, topographically specific chemical modification techniques, the identification of organelle-specific metabolism, permeabilized cell methodology, and yeast molecular genetics has contributed to revealing a diverse biochemical array of transport processes for lipids. Compelling evidence now exists for ATP-dependent, ATP-independent, vesicle-dependent, and vesicle-independent transport processes that are lipid and membrane specific. ATP-dependent transport processes include the transbilayer movement of phosphatidylserine and phosphatidylethanolamine at the plasma membrane and the transport of phosphatidylserine from its site of synthesis to the mitochondria. ATP-independent processes include the transbilayer movement of virtually all lipids at the endoplasmic reticulum, the movement of phosphatidylserine between the inner and outer mitochondrial membranes, and the transfer of nascent phosphatidylcholine and phosphatidylethanolamine to the plasma membrane. The ATP-independent movement of lipids between organelles is believed to be due to the action of lipid transfer proteins, but this still remains to be proved. Vesicle-based transport mechanisms (which are also inherently ATP dependent) include the transport of nascent cholesterol, sphingomyelin, and glycosphingolipids from the Golgi apparatus to the plasma membrane and the recycling of sphingolipids and selected pools of phosphatidylcholine from the plasma membrane to the cell interior. The vesicles involved in cholesterol transport to the plasma membrane are different from those involved in bulk protein transport to the cell surface. The vesicles involved in recycling sphingomyelin to and from the cell surface are different from those involved in the assembly of newly synthesized sphingolipids into the plasma membrane. The preliminary characterization of these lipid translocation processes suggests divergent rather than unifying mechanisms for lipid transport in organelle assembly.